2022
DOI: 10.1002/adfm.202203074
|View full text |Cite
|
Sign up to set email alerts
|

Flexible VO2 Films for In‐Sensor Computing with Ultraviolet Light

Abstract: With their unique advantages in portability, shape adaptability, and human friendly surfaces, flexible electronics pave the way for the implementation of wearable electronic textiles and human-machine interfaces. Although organic materials are promising for flexible devices because of the low-cost manufacturing and inherent flexibility, they meet challenges in harsh environments such as ultraviolet (UV) irradiation, which limits their applicability in UV sensors. Here, a flexible UV neuromorphic sensor is pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 69 publications
1
23
0
Order By: Relevance
“…Such a photoinduced structural transformation via atomic displacement can break the limit of the operation speed and energy in conventional PCMs, showing diffusional transformation. Furthermore, latest research has reported the applicability of nonvolatile optical switching to neuromorphic sensors. , Given these research trends, our experimental discoveries demonstrate that the MnTe polymorph can be a promising material for future application in ultrafast photonic memory and various optoelectronics devices.…”
Section: Discussionmentioning
confidence: 88%
“…Such a photoinduced structural transformation via atomic displacement can break the limit of the operation speed and energy in conventional PCMs, showing diffusional transformation. Furthermore, latest research has reported the applicability of nonvolatile optical switching to neuromorphic sensors. , Given these research trends, our experimental discoveries demonstrate that the MnTe polymorph can be a promising material for future application in ultrafast photonic memory and various optoelectronics devices.…”
Section: Discussionmentioning
confidence: 88%
“…After sensing with the device arrays, pistil signals in the memorized graphs are significantly enhanced, the petal signal is suppressed, and the surrounding signals are almost completely suppressed (Supplementary Movie 2 ). Subsequently, Supplementary Movie 2 is split into 74 frames with an interval of 20 ms, and the interframe differential computations are introduced to frame difference calculation of the memorized graphs 53 . The detailed explanation was described in Supplementary Note 2.…”
Section: Resultsmentioning
confidence: 99%
“…The study of VO 2 -based flexible strain sensors will promote the development of the next generation of multidimensional interaction technology that provides technical support for AI technology. Furthermore, the VO 2 flexible sensors were manufactured mainly by pulsed laser deposition, 34 photolithography, 35 etc. Although these methods can produce thinner, higher purity VO 2 films, they require high processing equipment and a special atmosphere.…”
Section: Introductionmentioning
confidence: 99%